Revealing relationships between microstructure and hardening nature of additively manufactured 316L stainless steel. (15th January 2021) - Cui, Luqing; Jiang, Shuang; Xu, Jinghao; Peng, Ru Lin; Mousavian, Reza Taherzadeh; Moverare, Johan
Abstract: Relationships between microstructures and hardening nature of laser powder bed fused (L-PBF) 316 L stainless steel have been studied. Using integrated experimental efforts and calculations, the evolution of microstructure entities such as dislocation density, organization, cellular structure and recrystallization behaviors were characterized as a function of heat treatments. Furthermore, the evolution of dislocation-type, namely the geometrically necessary dislocations (GNDs) and statistically stored dislocations (SSDs), and their impacts on the hardness variation during annealing treatments for L-PBF alloy were experimentally investigated. The GND and SSD densities were statistically measured utilizing the Hough-based EBSD method and Taylor's hardening model. With the progress of recovery, the GNDs migrate from cellular walls to more energetically-favourable regions, resulting in the higher concentration of GNDs along subgrain boundaries. The SSD density decreases faster than the GND density during heat treatments, because the SSD density is more sensitive to the release of thermal distortions formed in printing. In all annealing conditions, the dislocations contribute to more than 50% of the hardness, and over 85.8% of the total dislocations are GNDs, while changes of other strengthening mechanism contributions are negligible, which draws a conclusion that the hardness of the present L-PBF alloy is governed predominantly by GNDs. Graphical abstract: Unlabelled Image Highlights: Dislocation-type and their impacts on hardening nature of L-PBF alloys during annealing were studied. GND and SSD densities were statistically measured utilizing Hough-based EBSD method and Taylor's hardening model. Migration of GNDs during recovery leads to higher concentration of GNDs along new subgrain boundaries. SSDs decrease faster than GNDs during annealing, because SSDs largely depend on the release of thermal distortions. GND type dislocations governing the hardening nature of the present L-PBF alloys.